Lactylation may be a Novel Posttranslational Modification in Inflammation in Neonatal Hypoxic-Ischemic Encephalopathy - Zhou, Yue; Yang, Li; Liu, Xiaoying; Wang, Hao (Frontiers in Pharmacology, 2022)
Perinatal hypoxia-ischemia remains the most common cause of acute neonatal brain injury and is associated with a high death rate and long-term neurological abnormalities such as memory and cognitive deficits and dyskinesia. Hypoxia-ischemia triggers an inflammatory cascade in the brain that is amplified by the activation of immune cells and the influx of peripheral immune cells into the brain parenchyma in response to cellular injury. Thus, acute cerebral hypoxic-ischemic inflammation is a major contributor to the pathogenesis of newborn hypoxic-ischemic brain injury. Lactate is a glycolysis end product that can regulate inflammation through histone lactylation, a unique posttranslational modification that was identified in recent studies. The purpose of this review is to outline the recent improvements in our understanding of microglia-mediated hypoxic-ischemic inflammation and to further discuss how histone lactylation regulates inflammation by affecting macrophage activation. These findings may suggest that epigenetic reprogramming-associated lactate input is linked to disease outcomes such as acute neonatal brain injury pathogenesis and the therapeutic effects of drugs and other strategies in relieving neonatal hypoxic-ischemic brain injury. Therefore, improving our knowledge of the reciprocal relationships between histone lactylation and inflammation could lead to the development of new immunomodulatory therapies for brain damage in newborns.